Physicochemical and Biochemical Evaluation of Amorphous Solid Dispersion of Naringenin Prepared Using Hot-Melt Extrusion - Ishimoto, Kenji; Shimada, Yukiko; Ohno, Akane; Otani, Shuichi; Ago, Yukio; Maeda, Soya; Lin, Bangzhong; Nunomura, Kazuto; Hino, Nobumasa; Suzuki, Masayuki; Nakagawa, Shinsaku (Frontiers in Nutrition, 2022)
Naringenin (NRG) is a plant-derived flavonoid. Due to its antioxidant, anti-inflammatory, and analgesic activities it is beneficial to human health and is often used as a functional food; however, it has poor water solubility and low in vivo bioavailability. Therefore, the efficacy of NRG can be improved by enhancing its water solubility to increase gastrointestinal absorption. Conventional methods for the formulation of NRG are very complex and use toxic organic solvents, making them impractical for the production of functional foods. The objective of this study was to develop a safe and effective NRG-based functional food material. Previously, we established a technology to prepare amorphous solid dispersions (SDs) from functional food materials with poor water solubility and used hot-melt extrusion technology that is comparatively simple and does not involve the use of organic solvents. In this study, we prepared NRG SD and evaluated them both physicochemically and biochemically. NRG SD had superior water solubility and gastrointestinal absorption relative to native NRG and showed higher analgesic efficacy in rats than crystalline NRG. NRG SD was administered to mice in a mixed diet for 28 d, and organ weights and hematological/clinical biochemical parameters were assessed. NRG SD did not demonstrate severe adverse effects. The results suggest that NRG SD is a safe and highly efficacious formulation that can be used as a functional food material in the future.